STRATEGI KEMENANGAN ARIF MASKUR DALAM PEMILIHAN KEPALA DESA KESUBEN KECAMATAN LEBAKSIU KABUPATEN TEGAL PERIODE JABATAN TAHUN 2018-2024 - Cindy Septiani Saputri; Muhammad - Adnan; Neny - Marlina (Journal of Politic and Government Studies, 2022)
This study aims to explain and analyze the strategies used by Arif Maskur and his success team in the Election of the Head of Kesuben Village, Lebaksiu District, Tegal Regency in 2017. The method in this study uses a descriptive approach to the type of qualitative research. Data collection techniques were carried out through interviews. In analyzing Arif Maskur's winning strategy in the 2017 Kesuben Village Head Election, the researchers used three theories, namely political strategy theory, political marketing theory, branding theory and positioning. The results of the study explain that the Kesuben Village Head Election in 2017 went safely without any conflict even the Kesuben Village Head Election in 2017 received an award from the Lebaksiu District as the organizer of the safest village head election in Tegal Regency. The strategy used by Arif Maskur in the 2017 Kesuben Village Head Election is to take a personal approach to voters to convey their vision and mission. The success of Arif Maskur's political strategy is because Arif Maskur approaches all levels of society by conveying the vision, mission and program using a simple/legawa delivery without any lies. voters/society. The standby car which is one of Arif Maskur's programs is used by Arif Maskur and his success team to invite/lobby voters who are used as positioning, namely to maintain the focus of thoughts, orientation and awareness of the Kesuben Village community to keep in mind and direct the main references about the candidacy of Arif Maskur in the 2017 Kesuben Village Head Election. Meanwhile, Arif Maskur's success team used personal ties in the form of close family/friendship/community as a political strategy. Arif Maskur's success team also used a personal approach to voters, namely through door to door such as holding meetings, using campaign media in the form of billboards/banners containing information about Arif Maskur to convey Arif Maskur's vision, mission and work program to voters.